Preparation method of silicon-aluminum composite tanning agent

Through the preparation method of composite tanning agents of silicate and aluminum compounds, aluminosilicate composites with silicon as the framework are generated, which solves the problems of rare raw materials, high cost and poor performance in the preparation of chrome-free tanning agents, and achieves resistance Washed and soft and plump leather performance, with environmental protection and economical advantages.

CN119120794APending Publication Date: 2024-12-13SICHUAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310689363.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing preparation methods for chrome-free tanning agents have problems such as difficult to obtain raw materials, high cost, complex processing process, and the problems of silicon tanning agents and aluminum tanning agents being easily detanned and hardened during water washing and storage, which affects the resistance to washing and softness of the leather. performance.

Method used

Using the preparation method of composite tanning agent of silicate and aluminum compounds, aluminosilicate composite with silicon as the skeleton is generated by stirring and standing reaction at a constant temperature, inhibiting the formation of orthosilicate gel, fixing aluminum elements, and improving leather Wash resistance, and reduce costs and simplify processes through solid-state reactions.

Benefits of technology

It realizes the low-cost and simple process preparation of silicon-aluminum composite tanning agent, significantly improves the washing resistance and softness of the leather, avoids heavy metal pollution and the use of toxic and harmful ingredients, and the product is environmentally friendly and feasible.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of a silicon-aluminum composite tanning agent, which comprises the following steps: (1) a certain amount of silicate, an aluminum compound and an acidity regulator are weighed to form a mixed system, the molar ratio of Si to Al is 2: 1-1: 2, and the dosage of the acidity regulator is 5-15% of the mass of the aluminum compound; and (2) stirring the mixed system to react for 30-60 minutes at the temperature of 30-60 DEG C under the condition of constant temperature, then standing to react for 24-48 hours until the mixed system is naturally cooled to room temperature, and crushing to obtain the silicon-aluminum composite tanning agent. According to the silicon-aluminum composite tanning agent, the silicon compound reacts with the aluminum compound under the solid state condition, a silicon framework-loaded aluminum structure is formed under a certain pH value, and leather tanned by the obtained silicon-aluminum composite tanning agent is resistant to washing and good in softness and fullness. The raw materials for preparing the silicon-aluminum composite tanning agent are low in price, drying is not needed in the production process, and large-scale production and application are facilitated. The tanning agent does not contain toxic and harmful ingredients such as formaldehyde, hexavalent chromium and heavy metal, and has the characteristic of ecological environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of leather chemical material preparation, and specifically relates to a method for preparing a silicon-aluminum composite chrome-free tanning agent containing both silicon and aluminum elements. Background Art

[0002] Chrome tanning is the only tanning method known so far that uses a single tanning agent to make the shrinkage temperature of finished leather exceed 100°C. Chrome tanned leather not only has good wet heat stability, but also has excellent softness, fullness and water resistance. In addition, chrome tanning is simple to operate and has stable quality. Therefore, chrome tanning is currently the most important tanning method in leather processing. However, although trivalent chromium with tanning properties is used in the chrome tanning process, during the subsequent processing and use of the leather, the trivalent chromium will be oxidized into hexavalent chromium due to the influence of external temperature, pH and light. The toxicity of hexavalent chromium is significantly higher than that of trivalent chromium, and it has clear carcinogenicity and teratogenicity. As domestic and foreign consumers pay more and more attention to health, the hexavalent chromium risks that may be brought by chrome tanned leather have restricted the consumption of leather products, and the production of chrome-free tanned leather has received more and more attention.

[0003] Silicon is the element with a content only lower than oxygen in the earth's crust, and aluminum is the most abundant metal element in the earth's crust. Both of them have a wide range of sources. Studies have shown that both silicon and aluminum have a certain tanning effect and can tan raw hides into leather. However, both silicon tanning agents and aluminum tanning agents have very weak tanning properties. The shrinkage temperature of the finished leather after tanning is generally only about 70°C, and it is very easy to detannage after washing. At present, studies have used silicon and aluminum together to prepare tanning agents. Zhang Hui et al. dissolved silicon compounds and solvents in acid, and then added aluminum compounds to prepare them. After spray drying, chrome-free tanning agents can be obtained (Zhang Hui, Liu Zilong, Wang Xuechuan, Qiang Xihuai. A chrome-free tanning agent and its preparation method, CN 103980304 A). Che Jingtao et al. used organic acids to react with zeolite (containing silicon and aluminum elements) to make the aluminum element in the zeolite produce tanning properties, and obtained silicon-aluminum tanning agents with tanning properties (Che Jingtao, Jin Suyin. A leather tanning treatment method based on zeolite, CN 115232892 A). However, the raw materials required for the above method are not easy to obtain, and organic acids need to be used in the processing process, which is costly. In addition, the preparation process has many steps and is not easy to implement.

[0004] Therefore, developing a preparation technology for silicon-aluminum composite tanning agents with simple process, low cost and wide source of raw materials will provide a new option for the production of chrome-free tanned leather. Summary of the invention

[0005] The reason why leather tanned with aluminum tanning agent is easy to detannage is that aluminum, as an outer track type complex, has a much lower stability with collagen than the complex formed by chromium and collagen. During the process of washing or pickling, water or acid radicals easily replace collagen and combine with aluminum, resulting in detanning. The tanning effect of silicon tanning agent mainly comes from the silicon dioxide generated by the dehydration of orthosilicic acid. Silicon dioxide combines with collagen through multi-point hydrogen bonds. However, orthosilicic acid will repolymerize into a larger spatial network during the static process, making the finished leather hard. At the same time, the multi-point hydrogen bonds between silicon dioxide and collagen are not strong, which makes silicon tanned leather harden during storage and not resistant to water washing. However, silicon and aluminum are the second and third most abundant elements in the earth's crust, and their sources are very wide. In addition, aluminum is a light metal, and its use in tanning completely avoids the problem of heavy metal pollution. In order to solve the problems of silicon tanning agents and aluminum tanning agents, the inventors have conducted in-depth research on the disclosed tanning chemistry, coordination chemistry and silicon tanning and aluminum tanning related materials, and invented a preparation method for silicon-aluminum composite tanning agents.

[0006] Aluminum tanning agent is an outer orbital complex, which is its inherent property and cannot be changed. Therefore, its performance cannot be changed by modifying the traditional inorganic tanning agent, that is, changing the ligand and the central ion. Orthosilicic acid loses water to produce silicon dioxide, and it also has an inherent property to generate a huge spatial network structure over time, which cannot be prevented by changing the external environment. In order to overcome the problems of using silicon tanning agent and aluminum tanning agent separately, the inventor mixed them to prepare a composite tanning agent for use.

[0007] In the composite process of the two tanning agents, the silicon compound used is alkaline, while the aluminum compound used is acidic, and a chemical reaction will occur between the two. The present invention utilizes the acidity of the aluminum compound itself to suppress the tendency of orthosilicic acid to produce gel during the reaction of the silicon-aluminum composite tanning agent, and at the same time utilizes the mutual reaction of the two to generate a silicate aluminate complex with silicon as the skeleton, fixing aluminum on the silicon skeleton. There is no orthosilicic acid in the reaction product, thus overcoming the defect of silicon tanned leather becoming hard. Aluminum combines with silicon in the reaction, and the water washing resistance of the obtained leather is significantly improved. There is no significant change in the shrinkage temperature after washing with clean water for 2 hours, and there is no significant change in the appearance and performance of the leather.

[0008] On the basis of the above research, the inventors proposed a method for preparing a silicon-aluminum composite tanning agent, which is characterized in that the method for preparing the silicon-aluminum composite tanning agent comprises the following steps: (1) weighing a certain amount of silicate, aluminum compound and acidity regulator to form a mixed system, wherein the molar ratio of Si to Al is 2:1 to 1:2, and the amount of acidity regulator is 5-15% of the mass of the aluminum compound; (2) stirring the mixed system for reaction at a constant temperature of 30-60 °C for 30-60 min, and then standing the reaction for 24-48 h until it is naturally cooled to room temperature, and the silicon-aluminum composite tanning agent is obtained after crushing.

[0009] The method for preparing a silicon-aluminum composite tanning agent of the present invention is characterized in that the silicate is any one of sodium silicate, sodium silicate nonahydrate, sodium metasilicate or sodium fluorosilicate. The aluminum compound is any one of aluminum sulfate, aluminum sulfate 18hydrate, aluminum chloride hexahydrate, aluminum triformate or potassium aluminum sulfate dodecahydrate. The acidity regulator is any one of sodium hydroxide or sodium hydrogen sulfate.

[0010] The molar ratio of Si to Al in the reaction system is 2:1 to 1:2, which ensures that the content of silicon and aluminum is sufficient to form an aluminum compound with silicon as the skeleton. If the silicon content is too high and the aluminum content is too low, the orthosilicic acid in the product cannot be completely eliminated; if the silicon content is too low and the aluminum content is too high, the silicon skeleton cannot completely load the aluminum. Whether it is too much silicon or too much aluminum, the prepared tanning agent will have the defects of silicon tanning agent or aluminum tanning agent, that is, it is not resistant to water washing and hardens during storage.

[0011] The pH of the reaction system directly affects the occurrence of the reaction. If the pH is too high, aluminum tends to produce aluminum hydroxide and cannot be compounded with the silicon skeleton. Although a low pH can ensure the activity of aluminum, silicate is easy to gel, and the efficiency of the loading rate is greatly reduced. The preparation method of a silicon-aluminum composite tanning agent of the present invention is carried out under solid-state reaction, and the pH is also adjusted using solid acid or base, and its amount is 5-15% of the mass of the aluminum compound.

[0012] Since the preparation of the silicon-aluminum composite tanning agent is carried out in the solid state, the chemical reaction speed is slow, and the three solid reactants are not easy to mix evenly. Therefore, according to the particle size and properties of the selected product, it is necessary to stir at a constant temperature of 30-60 ° C for 30-60 min. If the stirring time is too short, the reactants cannot fully react. The reactants will react slowly during the stirring process, so it is necessary to heat appropriately at the beginning of the reaction. As the reaction proceeds, the heat generated by the reaction is sufficient to maintain the reaction, and the heating can be stopped. After stirring evenly, let it stand for 24-48 hours to allow the reaction to fully occur. During this process, the temperature of the reaction system gradually decreases until it cools naturally to room temperature.

[0013] The preparation method of a silicon-aluminum composite tanning agent provided by the present invention has the following advantages compared with existing products and technologies: 1. The raw materials used are widely available and low in cost. The reaction process is a solid-state reaction. The product production avoids the drying process. The operation is simple and convenient for large-scale production and application. 2. Compared with separate silicon tanning and aluminum tanning, the leather tanned by the silicon-aluminum composite tanning agent prepared by the present invention has excellent water-washing resistance, does not detannage after washing, and has good softness and fullness of the finished leather; 3. The product does not contain formaldehyde, hexavalent chromium, bisphenol compounds, heavy metals and other toxic and harmful ingredients commonly used in leather processing, and is eco-friendly. DETAILED DESCRIPTION

[0014] The following examples are given to illustrate the present invention in more detail. It is necessary to point out that the following examples cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technical personnel skilled in the art based on the above invention content still fall within the scope of protection of the present invention. Example 1

[0015] Mix appropriate amounts of sodium silicate, aluminum sulfate and sodium hydroxide, wherein the molar ratio of Si to Al is 2:1, and the amount of sodium hydroxide used is 5% of the mass of aluminum sulfate; react the mixed system at a constant temperature of 60°C with stirring for 50 min, then let it stand for 48 h until it cools naturally to room temperature, and then crush it to obtain a silicon-aluminum composite tanning agent. Example 2

[0016] Mix appropriate amounts of sodium silicate nonahydrate, aluminum sulfate 18hydrate and sodium hydroxide, wherein the molar ratio of Si to Al is 1:1, and the amount of sodium hydroxide used is 13% of the mass of aluminum sulfate 18hydrate; stir the mixed system at a constant temperature of 30°C for 60 minutes, then let it stand for 36 hours until it is naturally cooled to room temperature, and then crush it to obtain a silicon-aluminum composite tanning agent. Example 3

[0017] Mix appropriate amounts of sodium metasilicate, potassium aluminum sulfate dodecahydrate and sodium hydroxide, wherein the molar ratio of Si to Al is 1:2, and the amount of sodium hydroxide used is 15% of the mass of potassium aluminum sulfate dodecahydrate; stir the mixed system at a constant temperature of 50°C for 30 min, then let it stand for 24 h until it is naturally cooled to room temperature, and then crush it to obtain a silicon-aluminum composite tanning agent. Example 4

[0018] Mix appropriate amounts of sodium silicate nonahydrate, aluminum triformate and sodium bisulfate, wherein the molar ratio of Si to Al is 1.5:1, and the amount of sodium bisulfate is 7% of the mass of aluminum triformate; react the mixed system at a constant temperature of 40°C with stirring for 45 min, then let it stand for 40 h until it is naturally cooled to room temperature, and then crush to obtain a silicon-aluminum composite tanning agent. Example 5

[0019] Mix appropriate amounts of sodium fluorosilicate, aluminum chloride hexahydrate and sodium bisulfate, wherein the molar ratio of Si to Al is 1:1, and the amount of sodium bisulfate used is 7% of the mass of aluminum chloride hexahydrate; stir the mixed system at a constant temperature of 45°C for 40 min, then let it stand for 32 h until it is naturally cooled to room temperature, and then crush it to obtain a silicon-aluminum composite tanning agent. Example 6

[0020] Mix appropriate amounts of sodium silicate nonahydrate, aluminum chloride hexahydrate and sodium hydroxide, wherein the molar ratio of Si to Al is 1:1.5, and the amount of sodium hydroxide used is 9.5% of the mass of aluminum chloride hexahydrate; react the mixed system at a constant temperature of 40°C with stirring for 40 minutes, then let it stand for 44 hours until it is naturally cooled to room temperature, and then crush it to obtain a silicon-aluminum composite tanning agent. Example 7

[0021] Mix appropriate amounts of sodium silicate, potassium aluminum sulfate dodecahydrate and sodium hydroxide, wherein the molar ratio of Si to Al is 1:1 and the amount of sodium hydroxide used is 11% of the mass of potassium aluminum sulfate dodecahydrate; react the mixed system at a constant temperature of 35°C with stirring for 45 minutes, then let it stand for 38 hours until it is naturally cooled to room temperature, and then crush to obtain a silicon-aluminum composite tanning agent. Example 8

[0022] Mix appropriate amounts of sodium silicate, aluminum chloride hexahydrate and sodium hydroxide, wherein the molar ratio of Si to Al is 1:1 and the amount of sodium hydroxide used is 7.5% of the mass of aluminum chloride hexahydrate; react the mixed system at a constant temperature of 35°C with stirring for 50 min, then let it stand for 45 hours until it is naturally cooled to room temperature, and then crush it to obtain a silicon-aluminum composite tanning agent.

Claims

1. A method for preparing a silicon-aluminum composite tanning agent, characterized in that The preparation method of the silicon-aluminum composite tanning agent comprises the following steps: (1) weighing a certain amount of silicate, aluminum compound and acidity regulator to form a mixed system, wherein the molar ratio of Si to Al is 2:1 to 1:2, and the amount of the acidity regulator is 5-15% of the mass of the aluminum compound; (2) stirring the mixed system for reaction at a constant temperature of 30-60°C for 30-60 minutes, and then standing for reaction for 24-48 hours until it is naturally cooled to room temperature, and then crushing to obtain the silicon-aluminum composite tanning agent.

2. A method for preparing a silicon-aluminum composite tanning agent, characterized in that The silicate is any one of sodium silicate, sodium silicate nonahydrate, sodium metasilicate or sodium fluorosilicate.

3. A method for preparing a silicon-aluminum composite tanning agent, characterized in that The aluminum compound is any one of aluminum sulfate, aluminum sulfate 18hydrate, aluminum chloride hexahydrate, aluminum triformate, or aluminum potassium sulfate dodecahydrate.

4. A method for preparing a silicon-aluminum composite tanning agent, characterized in that The acidity regulator is any one of sodium hydroxide or sodium bisulfate.

Citation Information

Patent Citations

  • Inorganic composite animal tanbark material

    CN101033494A

  • Chrome-free metal compound tanning agent and preparation method thereof

    CN103667543A

  • Chromium-free tanning agent and preparation method thereof

    CN103980304A

  • Chromium-containing inorganic complexing chromium-containing tanning agent and preparation method thereof

    CN104726620A

  • Sewage treatment agent for treating thallium-containing wastewater

    CN115448433A